Calculation and modeling of the motion of charged particles in the quadrupole-cylindrical field - Kambarova, ZH.T.; Saulebekov, A.O (Publishing House of the KarSU named after E.A. Buketov, 2018)
The electron-optical scheme of the electrostatic energy analyzer on the basis of the quadrupole-cylindrical field is proposed. The outer electrode of the proposed energy analyzer has a cone profile, the generatrix of which is a small angle of inclination with respect to the symmetry axis of the mirror, equal to 1.75 deg. Calculation of particle-optical parameters of the energy analyzer is carried out. Advantages of this field are shown. Initial parameters of the motion of charged particles, optimal from the point of view of the luminosity and resolution ability are given.
Keywords: energy analyzer; electrostatic field; quadrupole-cylindrical mirror; corpuscular-optical parameters; angular focusing